2016
DOI: 10.1073/pnas.1523853113
|View full text |Cite
|
Sign up to set email alerts
|

Flight paths of seabirds soaring over the ocean surface enable measurement of fine-scale wind speed and direction

Abstract: Ocean surface winds are an essential factor in understanding the physical interactions between the atmosphere and the ocean. Surface winds measured by satellite scatterometers and buoys cover most of the global ocean; however, there are still spatial and temporal gaps and finer-scale variations of wind that may be overlooked, particularly in coastal areas. Here, we show that flight paths of soaring seabirds can be used to estimate fine-scale (every 5 min, ∼5 km) ocean surface winds. Fine-scale global positioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 44 publications
4
74
1
Order By: Relevance
“…While the temporal resolution of our tracking data was too coarse (4-to 12-min intervals between GPS locations) to identify fine-scale details of these flight paths, the highly consistent distribution of tracks across years suggests that persistent flight paths do occur. The literature suggests that social information exchange is most likely to be the driver of the consistency in the flight paths observed here; however, other factors such as avoidance of topographical features or olfactory cues may also influence these distributions (Pollonara et al 2015, Yonehara et al 2016. One other possible reason for increased flight through this area is that the west coast of the island faces the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 70%
“…While the temporal resolution of our tracking data was too coarse (4-to 12-min intervals between GPS locations) to identify fine-scale details of these flight paths, the highly consistent distribution of tracks across years suggests that persistent flight paths do occur. The literature suggests that social information exchange is most likely to be the driver of the consistency in the flight paths observed here; however, other factors such as avoidance of topographical features or olfactory cues may also influence these distributions (Pollonara et al 2015, Yonehara et al 2016. One other possible reason for increased flight through this area is that the west coast of the island faces the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 70%
“…There appear to be examples of both diagonal upwind flight and direct upwind flight by tacking. Further analysis of high temporal resolution tracks could provide details of fine-scale dynamic soaring flight maneuvers, estimates of fine-scale wind velocities [37], and more accurate airspeed and ground speed polars.…”
Section: Discussionmentioning
confidence: 99%
“…This same assumption was used as a basis to calculate fine-scale estimates of wind velocity from high resolution GPS measurements of the dynamic soaring maneuvers of seabirds [37]. Specifically, we modeled ground speed (magnitude of ground velocity) as a linear function of the component of wind velocity in the direction of ground velocity, W cos θ , where W is the wind speed at a reference height of 5 m (the median height of albatrosses observed near Bird Island) and θ is the relative angle between wind velocity and ground velocity [8].…”
Section: Methodsmentioning
confidence: 99%
“…Flight and drift paths of sea birds soaring and floating over the ocean surface enable measurement of fine-scale winds and currents. Yonehara et al (2016) and Goto et al (2017) found out that fine-scale flight trajectories by recording one position per second and minute provide 5-min to 1-h interval surface wind direction and speed along the trajectories. The birdestimated wind directions showed good agreement with those from satellite, although wind speeds were slower than satellite winds because sea birds flew at lower altitudes than 10 m at which satellite winds were calibrated.…”
Section: Development Of Biologging As An Ocean Observation Platform Fmentioning
confidence: 99%